How to raise a global citizen : for the parents of the children who will save the world - Davidson, Anna (Dorling Kindersley Limited, 2021)
"A cheerful, optimistic handbook for parents and carers shaping the next generation of responsible global citizens - ready to change the world for the better! Our children have the energy, capacity, and passion to create and nurture a global culture in which inclusion, acceptance, respect, and participation are the core values that underpin a human being's every interaction. As parents and carers, our job is to help our children take their first steps along that path. Raising truly globally minded, and socially conscious children happens at home and in the community. Children can be inspired, equipped, and mobilized to make a difference in the world. By encouraging values such as responsible and kind use of social media, respect, open mindedness, empathy, a sense of community, parents can help to shape a new generation of emotionally intelligent, outward-looking, politically ethical world citizens. Relevant to parents of children of all ages - from toddlers to teens - the book gives practical advice on how to talk to your children, the vocabulary to use, and activities and projects you can undertake with your children, from planting a tree to keeping a gratitude diary to cooking themed cuisines. And you'll find out how to model global citizenship through your own day-to-day actions"--Publisher's description.